Writing after Sidney the literary response to Sir Philip Sidney, 1586-1640 - Alexander, Gavin, Dr (Oxford University Press, 2006)
'Writing After Sidney' examines the literary response to Sir Philip Sidney, author of the 'Arcadia, Astrophil and Stella' and 'The Defence of Poesy', and the influential writer of the Elizabethan period.